c^2=a^2+b^2 then 4s(s−a)(s−b)(s−c)=
Question
Check here step-by-step solution of 'c^2=a^2+b^2 then 4s(s−a)(s−b)(s−c)=' question at Instasolv!
Fullscreen

(c^{2}=a^{2}+b^{2}) then ( 4 s(s-a)(s-b)(s-c)= )
1. (b^{2})
2) ( a^{2}+b^{2} )
3) ( frac{a^{2}}{b^{2}} )
4) ( a^{2}-b^{2} )

11th - 12th Class
Physics
Solution
65
Rating
4.0 (1 ratings)
c^2=a^2+b^2 then 4s(s−a)(s−b)(s−c)=
Fullscreen

( 2 s=a+b+c )
( s=(a+b+c) / 2 )
By Heron's formula
Area ( =(s(s-a)(s-b)(s-c)) 1 / 2 )
( a 2+b 2=c 2 )
( mathrm{Area}=1 / 2 * mathrm{a}^{*} mathrm{b} )
( (s(s-a)(s-b)(s-c)) 1 / 2=1 / 2 * a^{*} b )
( s(s-a)(s-b)(s-c)=a 2 b 2 / 4 )
( 4 s(s-a)(s-b)(s-c)=a 2 b 2 )

Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free